ANALISIS STRATEGI DALAM UPAYA MENINGKATKAN KINERJA KEMANDIRIAN KEUANGAN DAERAH PEMERINTAH PROVINSI KALIMANTAN TIMUR - Agus Tri Sulistiyo; Harianto Sulistiyo; A Faroby Falatehan (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT The mining sector is a leading sector that supports economic growth in the East Kalimantan region. However, the weakening of coal prices has led to economic sluggishness in East Kalimantan, even though the economic structure of East Kalimantan still relies on the mining sector. This condition has resulted in a decrease in the financial capacity of the local government, while the implementation of local government activities continues to increase. The measure of regional financial performance in implementing regional autonomy is by looking at the region's ability to finance development through Local Own-source Revenue (PAD) so that it no longer depends on central government funds in the form of Balance Funds. The general objective of this research is to formulate strategies to improve the Financial Performance of the East Kalimantan Provincial Government. The specific objective of this research is to develop strategic steps to improve the financial performance of the East Kalimantan Provincial Government using the Analytic Hierarchy Process (AHP). The strategy obtained from this research is to innovate services to increase PAD. Innovation is essential in public services because whatever the needs of the community, the East Kalimantan Provincial Government must respond quickly and accurately. Through innovation, it is hoped to be one of the ways to accelerate development effectively and efficiently. Keywords: AHP, PAD, financial performance, strategy